Analisis Total Kadar Asam Laktat Hasil Fermentasi Pare (Momordica charantia) Secara Spontan dengan Konsentrasi Garam Berbeda - Putri S. Noor; Wijanarka Wijanarka (Jurusan Biologi FMIPA Universitas Cenderawasih, 2021)
Bitter melon (Momordica charantia) is a traditional medicinal plant with great potential for treating diabetes due to its ability to lower blood sugar level. The bitter taste of this plant is attributed to its high nutrient and antioxidants content. Meanwhile, one of the ways to reduce the bitterness and improve its taste is through a spontaneous fermentation process with the right salt concentration. Therefore, this study aims to analyze the effect of different salt concentrations on the total lactic acid content of spontaneous bitter melon fermentation. This study was conducted using a completely randomized design (CRD) with 4 treatments and 3 replications. The treatments used included salt of different concentrations, namely: 3, 6, 9, and 12%. The bitter melon was fermented for 7 days and the parameter measured was the total lactic acid content through titration process. Furthermore, data were analyzed by ANOVA with 5% significance and the Duncan test was also carried out. The results showed different salt concentrations had a significant effect on lactic acid contents (P <0.05), with the highest being 0.4413% produced by 3% salt concentration treatment. These results are expected to contribute to the development of bitter melon utilization, as well as provide solutions, therefore, it becomes more effective and efficient food processing. Key words: bitter melon; fermentation; lactic acid; salt; spontaneous.